Penerapan Model G-MAPS Socioedu (Gamification-Mind Mapping-STAD Social Education) Dalam Pembelajaran IPS Kelas V SDN Kelayan Selatan 10 - Hayatun Syifa; Novi Handayani; Siti Rabbiatul Hasanah; Asniwati; Aldy Ferdiyansyah (Cahaya Smart Nusantara, 2025)
The low level of student learning independence in social studies at SDN Kelayan Selatan 10 has become a major issue affecting student engagement and responsibility in learning. This study aims to describe the application of the G-MAPS Socioedu model (Gamification–Mind Mapping–STAD Social education) and analyze its impact on students' learning independence in social studies. A descriptive qualitative approach using a case study method was employed in this research involving 20 fifth-grade students at SDN Kelayan Selatan 10. Data were collected through observation, interviews, and documentation. The results of the study indicate that the G-MAPS Socioedu model is capable of developing various indicators of student learning independence, such as curiosity, responsibility, discipline, and intrinsic motivation. Students become more active in discussions, independent in completing assignments, and enthusiastic about following the learning process. The existing technical obstacles do not diminish the success of this model in creating a collaborative, enjoyable learning atmosphere that encourages the development of students' independent learning potential.